Folk song today - Golež Kaučič, Marjetka (Traditiones (Ljubljana), 2005)
The paper deals with the question of the classification of the folk song today. With regard to its lost original context, has the folk song really become no more than an esthetic artifact, or have new circumstances reconstructed the context and thus added a new functional dimension to the folk song? In addition, the author discusses the new communication channels used to reintegrate the folk song in its traditional environment based on the example of the song "Riba Faronika nosi svet" (Faronika the Fish Bears the World)
Keywords: slovenske ljudske pesmi; folkloristics; folkloristika; aesthetics; estetika